2022
DOI: 10.1016/j.marpolbul.2022.113389
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19-derived plastic debris contaminating marine ecosystem: Alert from a sea turtle

Abstract: On 10 August 2021, a face mask (14 cm × 9 cm) was found in the feces of a juvenile green turtle, by-caught alive in a set net off the northeast coast of Japan. Although sea turtles have been monitored in this region over the last 15 years ( n = 76), face masks had never been found before the Covid-19 pandemic and this is the first detection. Fourier-transform infrared spectroscopy identified the mask as polypropylene. Estrogenic active benzotriazole-type UV stabilizers such as UV329 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Unfortunately, the accumulation of PPE on the main nesting beaches means that juvenile turtles are among the most threatened by plastic entanglement. Recently, Fukuoka et al (2022) found a face mask in the feces of a juvenile green turtle captured alive in a set net off the northeast coast of Japan. PPE represent a serious threat to marine turtle species in Indian waters.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the accumulation of PPE on the main nesting beaches means that juvenile turtles are among the most threatened by plastic entanglement. Recently, Fukuoka et al (2022) found a face mask in the feces of a juvenile green turtle captured alive in a set net off the northeast coast of Japan. PPE represent a serious threat to marine turtle species in Indian waters.…”
Section: Introductionmentioning
confidence: 99%
“…PPE are also able to liberate toxic chemical additives ( Hajiouni et al, 2022 ) and serve as a vector for contaminants ( Torres et al, 2021 ). The ingestion of face masks by marine organisms has also been documented in Brazil and Japan ( Neto et al, 2021 ; Fukuoka et al, 2022 ). Recently, Hiemstra et al (2021) and Ammendolia et al (2022) provided an overview of the impacts of PPE interaction with various types of aquatic and terrestrial animals through entrapment and entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported various organisms, such as birds and fishes, entrapped or entangled in PPE, as well as using them as nesting material ( Hiemstra et al, 2021 ; Mghili et al, 2021 ). Additionally, ingestion of face masks has been reported in top marine predators, such as the Magellanic penguin ( Spheniscus magellanicus ) and green turtle ( Chelonia mydas ) ( Fukuoka et al, 2022 ; Gallo Neto et al, 2021 ). The indirect impacts of PPE, such as the allocation of antibiotic resistance genes and the proliferation of potentially invasive species have been reported but further research is needed ( De-la-Torre and Aragaw, 2021 ; Zhou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the reported number of MPs detached from face masks varies depending on the environmental conditions, source, exposure time, and analytical procedures, among other factors. Face masks are also able to leach chemical contaminants, including heavy metals, dyes ( Ardusso et al, 2021 ; Sullivan et al, 2021 ), UV-stabilizers (UV329) ( Fukuoka et al, 2022 ), organophosphate esters ( Fernández-Arribas et al, 2021 ), and volatile organic compounds, such as alkanes, polycyclic aromatic hydrocarbons, and phthalate esters (PAEs) ( Jin et al, 2021 ). Particularly, PAEs have gained significant attention in recent studies due to their endocrine-disrupting effects ( Abtahi et al, 2019 ) and likeliness of being emitted from the surface of materials containing them ( Arfaeinia et al, 2020 ; Takdastan et al, 2021 ), such as face masks ( Min et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%